Molecular insights into postharvest seed coat darkening in common beans: a look beyond the P gene - Islam, Nishat S.; Dhaubhadel, Sangeeta (Frontiers in Plant Science, 2025)
Many market classes of common beans (Phaseolus vulgaris) have a significant reduction in crop value due to the postharvest darkening of the seed coat. Seed coat darkening is caused by an elevated accumulation and oxidation of proanthocyanidins (PAs). In common bean, the major color gene P encodes for a bHLH protein with its Psd allele controlling the postharvest slow darkening seed coat trait. In the present investigation, we determined that P/Psd, PvMYB3A, and PvWD9 are the essential components that form a protein complex and regulate PA biosynthesis in pinto beans. P does not bind with the PA biosynthetic gene Anthocyanin Reductase (PvANR) promoter but regulates its expression by interacting with PvMYB3A, which directly binds to the PvANR promoter. PvWD9 is an essential member of the core protein complex, which requires one or more additional plant components in order to interact with its partner proteins P and PvMYB3A and create a functioning complex. The Psd isoform affects the accumulation of PA by functioning in a similar manner to its isoform P, albeit at a lower efficiency. Understanding the regulation of PA biosynthesis in common beans helps to explain variances in seed coat color and issues associated with darkening after harvest.